Influence of methods of physical rehabilitation on quality of life in patients with toxic hepatitis - E.A. Shmatova; P.S. Nazar (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
He purpose was to improve the state of the quality of life in patients with chronic toxic hepatitis in-patient treatment phase by the use of comprehensive program of physical rehabilitation. We examined 84 patients, including 55 - and 29 men - women. Quality of life was measured using a questionnaire SF - 36. The data obtained were compared with those of healthy people - donors. Found that patients significantly reduced quality of life condition. A program of physical rehabilitation with the use of complex tools: physiotherapy, massage, segmental massage, treatment status, respiration system Yoga. On 10 - 15 day in-patient revealed a positive trend against other major symptoms of the disease. At 6 - 7 day disappeared signs asthenia, improved mood, appetite, depression and aggression disappeared, abdominal pain, heaviness in the right upper quadrant. It has also the normalization of the excretory function of the gastrointestinal - intestinal tract. Patients pay attention to the improvement of the symptoms: dyspnea, normalize heart rate, decrease pain and numbness in the legs.